Analysis Of Swept Time And Modal Parameter Effect On FRF’s Magnitude Error Of SDOF System Using Linear Swept-Sine Excitation - Asmara Yanto (Jurnal Momentum ISSN 1693-752X)
Random and swept-sine excitations are the most commonly used excitations in FRF (Frequency Response Function) measurement. There are various type of swept-sine excitation can be used, however, linear swept-sine is often used in FRF measurement. Linear swept-sine excitation is a sinusoidal excitation of which its requencies change linearly within time. This paper presents swept time and modal parameter effect on FRF’s magnitude error of SDOF (Single Degree of Freedom) system using linear swept-sine excitation. FRF’s magnitude error is focused at the peak of FRF’s magnitude error (system’s resonant frequency). Based on analysis study, the peak of FRF’s magnitude error of SDOF system is a function of swept time and system’s modal parameter (resonant frequency and damping ratio).